Foliar nutrient diagnosis in Paeonia ostii: an integrated DRIS-RN-CND approach for the fruit expansion stage - Zhu, MingWei; Zhao, Wei; Duan, Yu; Huang, Tao; Wang, YuXiao; Sun, LiYong; Li, ShuXian (Frontiers in Plant Science, 2025)
IntroductionFoliar nutrient diagnosis can facilitate an understanding of plant nutrient status, enabling the implementation of precise fertilization programs. As an emerging woody oil crop, Paeonia ostii, requires pressing research efforts to address the key agricultural challenge of achieving high-yield and high-efficiency cultivation.MethodsIn this study, the leaves were collected at the fruit expansion stage. The test materials were categorized into high- and low-yielding groups based on single plant yields, as determined by the Compositional Nutrient Diagnosis Inflection Point method. Finally, the low-yielding group was subjected to nutritional diagnosis using the Diagnosis and Recommendation Integrated System (DRIS) method.ResultsA significant difference in yield was observed between the two groups, with average yields of 123.2 and 55.3 g·plant-1. Appropriate nutrient ranges were established by the Range of Normality method. In the low-yielding group, Cu and Mn levels exceeded the optimal values, while the concentrations of other elements fell within the appropriate range. Through the DRIS method, it showed that the low-yielding group exhibited an excess of Cu and Mn, with elemental deficiencies ranked as follows: Ca > K > Mg > N > Zn > Fe > P. The combined DRIS Nutritional Imbalance Index (NBIm) values indicated that Ca deficiency was the most severe. DiscussionThe primary factors contributing to the reduced yield of P. ostii were the excesses of Cu and Mn and the deficiencies of Ca. In the future, greater attention should be paid to the issues of Ca supplementation and the management of localized heavy metals, with the aim of optimizing the production of P. ostii.